A case of pleural neurofibroma: A rare pleural tumor - Gupta, Amitesh; Mrigpuri, Parul; Kumar, Hemant (Indian Journal of Case Reports, 2018)
Neurofibromas (NFs) are benign tumors involving any nerve from the root level to the smallest branch. They may enlarge locally and cause a pressure effect on thoracic structures such as trachea, superior vena cava, and esophagus. Pulmonary and pleural involvement is very rarely seen. We have reported a case of a pleural effusion secondary to lymphatic obstruction due to remnant NF for which patient had undergone surgical resection in the past.